Decision regret among couples experiencing infertility: a mixed methods longitudinal cohort study - Rachel Cusatis; Colin Johnson; Katherine D. Schoyer; Shirng-Wern Tsaih; Joanna Balza; Jay Sandlow; Kathryn E. Flynn (BMC, 2023)
Abstract Background Decisions for how to resolve infertility are complex and may lead to regret. We examined whether couples and individuals who sought a consultation from a reproductive specialist for infertility later expressed decisional regret about their family-building choices and whether regret was associated with parental role, family-building paths, or outcomes. Methods This longitudinal mixed methods study included women and their partners who completed a questionnaire prior to their initial consultation with a reproductive specialist and 6 years later. The six-year questionnaire included the Ottawa Decision Regret Scale referencing "the decisions you made about how to add a child to your family." A score of 25+ indicates moderate-to-severe regret. Additional items invited reflections on family-building decisions, treatments, and costs. A systematic content analysis assessed qualitative themes. Results Forty-five couples and 34 individuals participated in the six-year questionnaire (76% retention rate), Half (n = 61) of participants expressed no regret, which was similar by role (median 0 for women and supporting partners, F = .08; p = .77). One in 5 women and 1 in 7 partners expressed moderate-to-severe regret. Women who did not pursue any treatment had significantly higher regret (median 15; F = 5.6, p < 0.01) compared to those who pursued IVF (median 0) or other treatments (median 0). Women who did not add a child to their family had significantly higher regret (median 35; F = 10.1, p < 0.001) than those who added a child through treatment (median 0), through fostering/adoption (median 0), or naturally (median 5). Among partners, regret scores were not associated with family-building paths or outcomes. More than one-quarter of participants wished they had spent less money trying to add a child to their family. Qualitative themes included gratitude for parenthood despite the burdensome process of family-building as well as dissatisfaction or regret about the process. Results should be confirmed in other settings to increase generalizability. Conclusion This longitudinal study provides new insight into the burden of infertility. For women seeking parenthood, any of the multiple paths to parenthood may prevent future decision regret. Greater psychosocial, financial, and decision support is needed to help patients and their partners navigate family-building with minimal regret.